Розв’язання задач економіко-математичного моделювання на основі дискретного геометричного моделювання виробничої функції - Пихтєєва, Ірина Вікторівна; Пыхтеева, Ирина Викторовна; Pykhtieieva, Iryna; Івженко, Олександр Васильович; Ивженко, Александр Васильевич; Ivzhenko, Oleksandr; Зінов'єва, Ольга Геннадіївна; Зиновьева, Ольга Геннадьевна; Zinovieva, Olha (My University, 2019)
UK: в роботі розглядається метод розв’язання задач економіко-математичного моделювання виробничих процесів, які виражають залежність результатів виробництва від витрат виробничих факторів. При аналізі попередніх досліджень авторами зазначено, що аналіз ефективності використання ресурсів здійснюється із використанням функції регресії. Але, якщо аналіз ефективності використання ресурсів не є змістом дослідження, то функція регресії може відігравати роль виробничої функції. Пропонований метод оснований на використанні дискретного геометричного моделювання виробничої функції. Для отримання рішення використовується дискретна апроксимація за критерієм дискретного методу найменших квадратів (ДМНК) регресивної моделі виробничої функції (ВФ). Авторами запропоновано кусково-лінійний розв’язок, що має кращий показник критерію. Застосування табличного процесора Excel дає проектувальнику можливість економії часу при проведенні обчислень і дозволяє вдосконалити вміння пошуку інформації для вирішення поставленого завдання. RU: в работе рассматривается метод решения задач экономико-математического моделирования производственных процессов, которые отображают зависимость результатов производства от затрат производственных факторов. При анализе предыдущих исследований авторами отмечено, что анализ эффективности использования ресурсов осуществляется с использованием функции регрессии. Применение, при этом, табличного процессора Excel дает проектировщику возможность экономии времени при проведении вычислений и позволяет усовершенствовать умение поиска информации для решения поставленной задачи. EN: In work the method of the decision of tasks of economic-mathematical modeling of productions which display dependence of results of manufacture on expenses of production factors is considered. At the analysis of the previous researches by authors it is marked, that the analysis of efficiency of use of resources is carried out with use of function of regress. But, if the analysis of efficiency of use of resources is not the maintenance of research function of regresses can be submitted as production function. The offered method is based on use of discrete geometrical modeling of production function. For reception of the decision discrete approximation by criterion of a discrete method of the least squares (DMLS) of regressive model of production function (PF) is used. Authors the piecewise-linear decision of a task in view which has the best parameter of criterion is offered. A technique for solving analysis problems in modeling economic processes is proposed. The use of information technologies contributes to the introduction of modern methods of data analysis and forecasting. A specialist, at the same time, only research work remains - setting the task, assessing the quality of the models obtained. To do this, you must have adequate training in the field of application of computing technology in the construction of economic and mathematical models, data processing and forecasting. At the same time, using the Excel spreadsheet processor gives the designer the opportunity to save time during the calculations and allows you to improve the ability to search for information to solve the problem.
Решение задач экономико-математического моделирования на основе дискретного геометрического моделирования производственной функции
The decision of tasks of economic-mathematical modelling on the basis of discrete geometrical modelling production function
Keywords: корекція; дискретна апроксимація; кусково-лінійна регресія; виробнича функція; метод найменших квадратів; дискретний точковий ряд